Maternal Thyroid Function During Pregnancy and the Child’s Linguistic and Sensory Development in the Northern Finland Birth Cohort 1986 - Päkkilä, Fanni; Männistö, Tuija; Hartikainen, Anna-Liisa; Suvanto, Eila (Frontiers in Endocrinology, 2018)
Background: Maternal hypothyroidism and hypothyroxinemia are associated with poor neuropsychological development in children. Previous research is lacking on whether maternal thyroid dysfunction affects sensory and linguistic development in childhood. Methods: The Northern Finland Birth Cohort 1986 included all births within a year (9362 women, 9479 children) from the two northernmost Finnish provinces. Maternal serum samples (n=5791) were obtained in early pregnancy and analyzed for TSH, free T4, and thyroid peroxidase antibodies (TPO-Abs). Five thousand, three hundred, and ninety-one parents evaluated their child’s sensory and linguistic development at seven years old via a questionnaire (excluding children with an intelligence quotient ≤ 85). The prevalence of sensory and linguistic impairments was compared between mothers with and without thyroid dysfunction. Results: Children of hypothyroid and hypothyroxinemic mothers had an increased prevalence of vision impairment compared to those of euthyroid mothers (10.8% and 11.7%, respectively, versus 6.5%), but the difference was not significant. There were no statistically significant differences in the prevalence of sensory or linguistic impairment between children of mothers with and without thyroid dysfunction. All results remained similar after excluding TPO-Ab-positive mothers and premature children. Conclusions: We did not find an association between maternal thyroid dysfunction during pregnancy and sensory and linguistic development impairment in childhood. A somewhat higher prevalence of vision impairment was seen in children of hypothyroid and hypothyroxinemic mothers, which merits further research.